Engineering modified neutrophil sound-sensitive agent drug delivery system and application thereof - LUO TENGSHUO; WANG YEYING; SUN LEI; ZHOU JING'E; WANG JING; DING NANJIN; YAN ZHIQIANG; WANG ZHEHAO; LUO SHENGGEN (2021)
The invention discloses an engineering modified neutrophil sound-sensitive agent delivery system. The delivery system is composed of neutrophils and nanoparticles formed by oxygen-containing perfluorinated compounds and sound-sensitive agents loaded into the neutrophils in an active targeting mode. The invention further discloses application of the engineering modified neutrophil sound-sensitive agent drug delivery system in preparation of drugs and/or reagents for diagnosing and/or treating tumors. The neutrophils are subjected to nano-engineering modification, so that the neutrophils have the multi-stage targeting capacity of targeting tumor inflammation parts and targeting tumor cells, and the functions of relieving tumor hypoxia, sonodynamic therapy and ultrasonic imaging are achieved. The biocompatibility of the drug can be remarkably improved, the treatment effect of the drug is effectively improved under the ultrasonic condition, tumor tissues are eliminated, the survival time of tumor-bearing mice is